Edukasi Virtual Ketahanan Ekonomi Keluarga Dalam Lingkup Edukasi Makanan Gizi Untuk Kesehatan - Sri Indah; Hendrik Suhendri; Willy Tri Hardianto; Poppy Indrihastuti; Risnaningsih (WIDA Publishing, 2022)
Limited knowledge and low levels of healthy living behavior have a significant impact on nutrition, health, and the economic well-being of families. To address these issues, this community service focused on problem solving, namelu through a virtual education method and self-reflection. Having 40 participants from PKK members in Precet Village, it was conducted through group discussions. The aims of this activity are to (1) improve awareness of balanced nutrition, nutrition, and the benefits of local food, and (2) to increase awareness of local food processing as a means of ensuring nutritional and economic security. This discussion then concluded that educational methods are quite effective at increasing knowledge. Additionally, the distribution of educational contents virtually ensures that the information presented is understood, as it is an audio-visual medium.